2015
DOI: 10.1038/ncomms9087
|View full text |Cite
|
Sign up to set email alerts
|

Nek2 activation of Kif24 ensures cilium disassembly during the cell cycle

Abstract: Summary Many proteins are known to promote ciliogenesis, but mechanisms that promote primary cilia disassembly prior to mitosis are largely unknown. Here, we identify a mechanism that favors cilium disassembly and maintains the disassembled state. We show that co-localization of the S/G2 phase kinase, Nek2, and Kif24 triggers Kif24 phosphorylation, inhibiting cilia formation. We show that Kif24, a microtubule depolymerizing kinesin, is phosphorylated by Nek2, which stimulates its activity and prevents the outg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
169
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 133 publications
(180 citation statements)
references
References 51 publications
11
169
0
Order By: Relevance
“…Three possible mechanisms by which Nek2A-phosphorylated SuFu might inhibit Gli2 activity have been proposed: one mechanism is when stable SuFu tethers more Gli2 in the cytoplasm and prevents the latter from entering the nucleus; another mechanism is when phosphorylated SuFu translocates into the nucleus and inhibits Gli2 transcriptional activity in the nucleus; and the third mechanism is when phosphorylated SuFu recruits SAP18 to suppress Gli2 transcriptional activity in the nucleus. A recent study reported that Nek2 may phosphorylate Kif24, a microtubule depolymerizing kinesin, to prevent the outgrowth of cilia in proliferating cells [51]. In order to induce sufficient cilia for observation, we employed murine siRNA targeting NEK2 to address the localization ability of SuFu in primary cilia of NIH3T3 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Three possible mechanisms by which Nek2A-phosphorylated SuFu might inhibit Gli2 activity have been proposed: one mechanism is when stable SuFu tethers more Gli2 in the cytoplasm and prevents the latter from entering the nucleus; another mechanism is when phosphorylated SuFu translocates into the nucleus and inhibits Gli2 transcriptional activity in the nucleus; and the third mechanism is when phosphorylated SuFu recruits SAP18 to suppress Gli2 transcriptional activity in the nucleus. A recent study reported that Nek2 may phosphorylate Kif24, a microtubule depolymerizing kinesin, to prevent the outgrowth of cilia in proliferating cells [51]. In order to induce sufficient cilia for observation, we employed murine siRNA targeting NEK2 to address the localization ability of SuFu in primary cilia of NIH3T3 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Cilium disassembly requires the destabilization and de-polymerization of axonemal microtubules, and two members of the Kinesin-13 family of de-polymerizing kinesins, Kif2a and Kif24, are implicated in cilium disassembly 6264 (Fig. 3).…”
Section: Cilium Disassemblymentioning
confidence: 99%
“…As for CP110 loss, ablation of Kif24 results in inappropriate assembly of cilia in proliferating cells, although it does not regulate centriole length. The microtubule de-polymerizing activity of Kif24 is enhanced by Nek2- mediated phosphorylation 64 . Nek2 is expressed during S and G2 phase, ensuring that Kif24 is active in cells that lack cilia.…”
Section: Cilium Disassemblymentioning
confidence: 99%
See 2 more Smart Citations